2021
DOI: 10.3389/fnins.2021.758677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effects of Glatiramer Acetate Treatment on Amyloid Deposition and Tau Phosphorylation in the 3xTg Mouse Model of Alzheimer’s Disease

Abstract: Neuroinflammation driven by the accumulation of amyloid β (Aβ) can lead to neurofibrillary tangle formation in Alzheimer’s Disease (AD). To test the hypothesis that an anti-inflammatory immunomodulatory agent might have beneficial effects on amyloid and tau pathology, as well as microglial phenotype, we evaluated glatiramer acetate (GA), a multiple sclerosis drug thought to bias type 2 helper T (Th2) cell responses and alternatively activate myeloid cells. We administered weekly subcutaneous injections of GA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…4 ). These findings highlight the value of assessing Tau pathology through multiple approaches [ 55 ] and suggest a potential disease-modifying benefit of our repopulation paradigm.…”
Section: Discussionmentioning
confidence: 90%
“…4 ). These findings highlight the value of assessing Tau pathology through multiple approaches [ 55 ] and suggest a potential disease-modifying benefit of our repopulation paradigm.…”
Section: Discussionmentioning
confidence: 90%
“…These studies found an increase in the Th2-derived regulatory anti-inflammatory cytokines Interleukin-4 (IL-4) and Interleukin-10 (IL-10), primarily around Aβ plaques, and a reduction in proinflammatory mediators (i.e., TNFα, IL-6) [31,104,105,125]. In fact, several studies found that there is an important role for GAdriven immunomodulation, affecting both the central and peripheral immune responses, leading to regulation and repair causing Aβ removal in AD models [31,32,95,124,126,127]. One study found that GA-activated central immune cells, such as microglia, degraded, engulfed, and cleared soluble fibrillar Aβ plaques [125].…”
Section: Role Of Ga In Repair Regeneration and Cognitive Preservation...mentioning
confidence: 99%
“…The new phenotypes were associated with proliferation and survival of oligodendrocytes, preserved synaptic processes and increased levels of neural progenitor cells, showing signs of enhanced neurogenesis and neuroprotection [95,127]. [126] All studies utilized transgenic models of AD. Animals in the treatment groups received 100 µg/s.c./qw, unless otherwise specified; AD: Alzheimer's disease; Aβ: Aβ; MWMT: Morris water maze test; RAWM: radical arm water maze; SGZ: subgranular zone; m: male; qm: monthly; BMT: Barnes maze test; MΦ BM : bone-marrow-derived monocytes/macrophages; DG: dentate gyrus; MEA: multi-electrode analysis; f/oAβ 42 : fibrillar/oligomeric Aβ 42 ; IOP: intraocular pressure; RT-PCR: real time-polymerase chain reaction; WB: Western blot; EGR1: early growth response gene 1; MMP9: matrix metallopeptidase 9; FAD-familial Alzheimer's disease; DT-diphtheria toxin.…”
Section: Role Of Ga In Repair Regeneration and Cognitive Preservation...mentioning
confidence: 99%
See 2 more Smart Citations